Perceptions of Saudi EFL Teachers on the Adequacy of Textbooks - Somaili, Maryam Hassan; Alhamami, Munassir (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study evaluated elementary school EFL textbooks (We Can Series) from the perspectives of male and female teachers in Saudi Arabia. A quantitative approach was used, with data collected through a questionnaire. The questionnaire, adopted from Alharbi (2017), consisted of 49 items arranged into five textbook evaluation criteria: layout and design, textbook objectives, language methods and activities, language skills, and general evaluation. The questionnaire was administered online using Google Forms to 51 primary school teachers. The results of the study revealed that the primary-stage textbooks are efficient in terms of layout and design. The objectives are stated and highlighted in each section, all language skills are included, there are an appropriate number of activities and exercises, and there are instructions beside each part of the content. However, the study also found that the book's objectives, exercises, skills, and teaching methods are inappropriate for learners' needs at these levels; the number of lessons allocated each week is insufficient for the book's content; there is no logical progression between topics; and supplemental materials such as test models are not available. Additionally, there was a lack of cohesion and sequencing between textbooks in the